The effects of wheat and crystalline amino acids on nursery and finishing pig growth performance and carcass characteristics - D L Goehring; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
Two experiments were conducted to evaluate the effects of wheat and crystalline amino acids on growth performance of nursery and finishing pigs. In Exp. 1, a total of 192 pigs (PIC, 337 × 1050, initially 26.7 lb BW) were used in a 21-d nursery study. Pigs were allotted to pens by initial BW, and pens were assigned to 1 of 4 dietary treatments in a completely randomized design with 6 pigs per pen and 8 replications per treatment. Treatments included: (1) corn-soybean meal diet, (2) diet 1 with wheat replacing approximately 50% of the corn, (3) wheat replacing 100% of the corn in diet 1 with high amounts of crystalline amino acids, and (4) diet 3 with 5% more SBM and lower crystalline amino acids. Overall, (d 0 to 20), no growth performance differences were found when replacing 50% of corn with wheat (P>0.75), but tendencies for reduced ADG (linear, P<0.08) were observed when replacing 100% corn with wheat. Replacing 100% of corn with wheat improved (linear, P<0.05) caloric efficiency on an ME basis and tended to improve (linear, P<0.07) caloric efficiency on an NE basis. Adding more soybean meal to all wheat diets tended to improve (P<0.07) F/G and improved (P<0.03) caloric efficiency on an NE basis.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Amino acids; Finishing pig; Nursery pig; Wheat